2015
DOI: 10.1155/2015/161869
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Biomechanical Properties in Myopic Eyes Measured by a Dynamic Scheimpflug Analyzer

Abstract: Purpose. To evaluate the corneal biomechanical parameters in myopic and emmetropic eyes using Corneal Visualization Scheimpflug Technology (CorVis ST). Methods. 103 myopic and emmetropic eyes of 103 patients were examined. Corneal biomechanical parameters, axial length, and mean keratometry were measured using CorVis ST, IOL Master, and topography, respectively. Corneal biomechanical properties were compared within four groups. Bivariate correlation analysis was used to assess the relationship between corneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
30
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 33 publications
9
30
3
Order By: Relevance
“…The severe and high myopia groups had a smaller A2-length than other groups. These findings are not in line with those from Wang et al [21], their study did not show the difference of A2-velocity between groups. Another study, consistent with our results, showed high myopia had greater A2-velocity compared to either low to moderate myopia or emmetropia using the Corvis ST. [20] A2-time, A2length and A2-velocity were significantly positively correlated with SE and negatively correlated with AL, this agreed with the ANOVA in the present study.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…The severe and high myopia groups had a smaller A2-length than other groups. These findings are not in line with those from Wang et al [21], their study did not show the difference of A2-velocity between groups. Another study, consistent with our results, showed high myopia had greater A2-velocity compared to either low to moderate myopia or emmetropia using the Corvis ST. [20] A2-time, A2length and A2-velocity were significantly positively correlated with SE and negatively correlated with AL, this agreed with the ANOVA in the present study.…”
Section: Discussioncontrasting
confidence: 92%
“…DA is the deformation amplitude at highest concavity and is regarded as a surrogate for corneal stiffness. [18,21,28] A higher DA value would represent a softer cornea due to a lower resistance to deformation. [28,29] Our findings showed that the higher the degree of myopia or the longer the axial length, the softer of the cornea is, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ORA parameters are affected by various baseline factors such as refraction, 8,9 axial length, [21][22][23][24] age, 23 IOP, 23 corneal curvature, 23 and central corneal thickness (CCT). 25 Parameters measured with the Corvis ST are associated with the axial length, 26 age, 27,28 diabetes, 29 IOP, 13,25,[30][31][32] corneal curvature, 26,33 and CCT. 34 To clarify the association between ocular disorders and corneal biomechanics, it is essential to adjust for the possible confounding effects of factors that potentially affect corneal biomechanical parameters.…”
mentioning
confidence: 99%